Nucleoside Analogs with Selective Antiviral Activity against Dengue Fever and Japanese Encephalitis Viruses - Zandi, Keivan; Bassit, Leda; Amblard, Franck; Cox, Bryan D.; Hassandarvish, Pouya; Moghaddam, Ehsan; Yueh, Andrew; Libanio Rodrigues, Gisele Olinto; Passos, Ingredy; Costa, Vivian V.; AbuBakar, Sazaly; Zhou, Longhu; et al. (American Society for Microbiology, 2019)
Dengue virus (DENV) and Japanese encephalitis virus (JEV) are important arthropod-borne viruses from the Flaviviridae family. DENV is a global public health problem with significant social and economic impacts, especially in tropical and subtropical areas. JEV is a neurotropic arbovirus endemic to east and southeast Asia. There are no U.S. FDA-approved antiviral drugs available to treat or to prevent DENV and JEV infections, leaving nearly one-third of the world’s population at risk for infection. Therefore, it is crucial to discover potent antiviral agents against these viruses. Nucleoside analogs, as a class, are widely used for the treatment of viral infections. In this study, we discovered nucleoside analogs that possess potent and selective anti-JEV and anti-DENV activities across all serotypes in cell-based assay systems. Both viruses were susceptible to sugar-substituted 2=-C-methyl analogs with either cytosine or 7-deaza-7-fluoro-adenine nucleobases. Mouse studies confirmed the anti-DENV activity of these nucleoside analogs. Molecular models were assembled for DENV serotype 2 (DENV-2) and JEV RNA-dependent RNA polymerase replication complexes bound to nucleotide inhibitors. These models show similarities between JEV and DENV-2, which recognize the same nucleotide inhibitors. Collectively, our findings provide promising compounds and a structural rationale for the development of direct-acting antiviral agents with dual activity against JEV and DENV infections.